Geochemical, mineralogical, and petrological characteristics of the Cretaceous coal from the middle Benue Trough Basin, Nigeria: implication for coal depositional environments (2022)
The Benue Trough Basin (BTB) of Nigeria is geologically and geo-morphologically subdivided into upper, middle, and lower segments. The BTB is the subject of geological research due to its rich coal deposits that have the potential for oil and gas. The purpose of the present study is to examine the origins, depositional environments, and thermal history of the selected coals and the processes that influence their quality. Coal samples from different open cast coal mines in the middle BTB were examined using proximate and ultimate, x-ray diffraction (XRD), x-ray fluorescence (XRF), laser ablation induced coupled plasma (LA-ICPMS), and petrographical analyses. The coal samples contained mainly quartz, kaolinite, and organic carbon. The XRD spectra peaks revealed the triclinic and monoclinic structure of kaolin. The SiO2/Al2O3 ratios confirmed the dominance of quartz and kaolinite. The Ni/Co versus V/Cr, Cu/Zn, and V/Mo values in the studied coals suggest oxic depositional environments, whereas the V/(Ni + V) and V/(V + Cr) values indicate oxic to suboxic conditions. The Ce/Ce∗ values are slightly below 1, which indicates a suboxic depositional environment. Maceral texture is indicative of transformations from sub-bituminous to high volatile C or B bituminous coal. The maceral components and mineral matter (≥10%) of the studied coals imply deposition in the planar margin mire, and a river system of planar margin mire environments, respectively. The high gelification index (GI) and tissue preservation index (TPI) values indicate peat accumulation developed within a wet forest swamp. The ternary diagram of the maceral component suggests deposition in a wet moor environment with intermittent moderate to high flooding episodes. The studied coals are sub-hydrous vitrinite inferring hydrogen-poor and thermally immature characteristics. The low V and Ni contents, low H/C and high O/C, indicate Type Ⅲ terrestrial organic matter with the potential to generate gaseous hydrocarbons. The investigated coals were deposited by the river within telmatic, limnic, and limno-telmatic zones in the planar margin mire depositional environments. Overall, the integrated petrologic and geochemical data used in this study provides a reliable approach for the assessment of coal depositional environments.